Inclusion of wet corn gluten feed with physically effective neutral detergent fiber and the resulting effects on production - Sullivan, Michelle Lea (Kansas State University, 2011)
Wet corn gluten feed (WCGF) is commonly included in lactation rations for dairy cattle. Research at Kansas State University has shown that increasing WCGF inclusion decreased ruminal pH. Lack of adequate particle size may result in this decrease and can impact efficiencies, animal health and longevity. A study was conducted to look at the effects of feeding WCGF while maintaining > 10% of particles > 19 mm across diets. We hypothesized that as WCGF increased, DMI and milk yield would increase while ruminal pH would be maintained. Seven ruminally-cannulated, lactating Holstein cows were used in an incomplete 4 × 4 Latin square design with treatments of 0, 12.4, 24.5 or 35.1% WCGF across 4 periods of 21 d. Alfalfa hay was used to maintain particle size. All diets met particle size goals; however, as WCGF increased, the proportion of particles > 19 mm decreased (P = 0.01) and cows changed their sorting behavior in favor of particles > 19 mm (P = 0.03) and against particles on the bottom screen (P < 0.01) and pan (P = 0.01). As WCGF increased, ruminal pH and ECM/DMI were not affected, yet DMI (P = 0.02) and milk yield (P = 0.02) increased quadratically. Milk protein, lactose and fat concentrations were not affected; however, milk protein (P = 0.004; linear) and lactose (P = 0.02; quadratic) yields increased. In a separate study, active dry yeast (ADY) products, commonly used in the dairy industry to support ruminal health, were evaluated for product guarantees and effects of storage and storage medium. Few products received through normal distribution met product guarantees (1 of 6; experiment 1) and after 3 mo of storage cell viability dropped significantly (P < 0.01). In the second experiment, products were stored in ground corn or in a vitamin-trace mineral mix (VTM). Depressions in viability caused by high-temperature storage were partially mitigated when ADY products were stored with a VTM. Although both mediums resulted in lower cell viabilities after storage at 40ºC, VTM cell viabilities were significantly (P = 0.02) higher than ground corn.
Keywords: peNDF; Wet corn gluten feed; Ruminal pH; Active dry yeast; Viability; Animal Sciences (0475)